Unraveling federal award terminations: evidence from the Louis Stokes Alliances for Minority Participation - Barros-Bustos, Solange; Chicas-Mosier, Ana M. (Frontiers in Education, 2026)
The National Science Foundation (NSF) ended funding for more than 1,600 projects as of 8 July 2025. Approximately 5% of the terminated NSF grants were of Louis Stokes Alliances for Minority Participation. NSF LSAMP can be used to understand the federal decision-making in determining which grants to terminate or maintain. We assessed eight metrics: (1) total cost of an award, (2) the amount already spent on an award, (3) proportion remaining on an award, (4) number of months remaining in an award, (5) the type of award, (6) location of award, (7) inclusion in the Ted Cruz-led senate investigation, and (8) verbiage in the abstract. We found no correlations between the data and project terminations. We find that the terminations of LSAMP grants were not evidence based and therefore should be overturned per existing precedent and in accordance with the Administrative Procedure Act (1946). We recommend that higher education institutions use the presented data as evidence for litigation and LSAMP award reinstatement.